2023
DOI: 10.1039/d3ra03213b
|View full text |Cite
|
Sign up to set email alerts
|

Fast-response photothermal bilayer actuator based on poly(N-isopropylacrylamide)–graphene oxide–hydroxyethyl methacrylate/polydimethylsiloxane

Abstract: Schematic illustration of the preparation of the PNIPAM-based composite hydrogel and the driving behavior of the PGH/PDMS photothermal bilayer actuator when switching between a light/hot and cold environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Similarly, Li et al have designed a bilayer actuator by a photothermally sensitive hydrogel layer and PDMS layer. 61 The hydrogel was created by the thermally sensitive hydrogel PNIPAM with hydroxyethyl methacrylate (HEMA) and GO as photothermal materials. The HEMA effectively drives water molecules inside the hydrogel, which causes bending.…”
Section: Recent Strategies For Designing Photothermal Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Li et al have designed a bilayer actuator by a photothermally sensitive hydrogel layer and PDMS layer. 61 The hydrogel was created by the thermally sensitive hydrogel PNIPAM with hydroxyethyl methacrylate (HEMA) and GO as photothermal materials. The HEMA effectively drives water molecules inside the hydrogel, which causes bending.…”
Section: Recent Strategies For Designing Photothermal Actuatorsmentioning
confidence: 99%
“…The photoresponsive components such as MXenes, 54,55 graphene, 56,57 carbon-based materials, 58 and graphene and their derivatives 59,60 have lower CTE and are used as a light absorption layer. Polymers such as polydimethylsiloxane (PDMS), 61,62 polyvinylidene fluoride (PVDF), 63 polyethylene (PE), 64 and polycarbonate (PC) 65 have high CTE and are used as thermal expansion layers. The high CTE layer expands asymmetrically due to heat generated by the low CTE layer upon exposure to light.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several researchers have reported thermo- and photo-responsive composite hydrogels by loading GO into the PNIPAM matrix. 156,159,165,276,341 The out-of-plane deformation can be achieved by local light irradiation 7,163 assemblies of GO-PNIPAM active layer with a non-thermo-responsive passive layer 342,343 or by introducing a gradient distribution of GO within the matrix. 160,161 Other photothermal additives such as AuNP and WS 2 inorganic compounds can cooperate with PNIPAM hydrogel matrices using similar methods.…”
Section: Shape Morphing Behaviors Of Composite Hydrogels Controlled B...mentioning
confidence: 99%
“…2D materials such as graphene and MXene with negative or relatively low coefficients of thermal expansion (CTE) (−3.26 × 10 −6 and 2.26 to 17.83 ×10 −6 K −1 , respectively) [235][236][237] can be combined with organic polymers, such as polytetrafluoroethylene (PTFE) and PDMS, with the CTE values of 3.56 × 10 −4 and 3 × 10 −4 K −1 , respectively, to trigger a programmable thermal actuation behavior. [212,238] While a heat is applied, the thermal coefficient mismatch leads to the desired actuation. [239] Hu et al reported reversible photothermal TRAs based on a bimorph structure of rGO/CNT and PDMS layer, demonstrating a large deformation angle of 479°under only 3.6 s sunlight irradiation.…”
Section: Thermo-responsive Actuatormentioning
confidence: 99%
“…[195] A bilayer actuator composed of PNIPAM hybridized with GO layer and hydroxyethyl methacrylate layer for photothermal effect and improved water transport, respectively, demonstrated reversible bending behavior upon thermal cycling. [238] Wang et al endowed the elastin-like polypeptide hydrogel actuators with grapheneenabled light-controllability, whose mechanical motions were readily tunable by the light intensity and irradiation direction (Figure 8c). [199] Thermotropic liquid crystalline elastomers (LCEs) are another platform for thermo-responsive soft actuation exhibiting a sizeable stimuli response.…”
Section: Thermo-responsive Actuatormentioning
confidence: 99%